Nilai-Nilai Sosial dan Keagamaan dalam Tradisi Nukup Lubang di Desa Maras Jauh Kecamatan Semidang Alas Maras - Yansen Paul; Irwan Satria; Nurniswah Nurniswah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The Kaiak Basuah Tangan Nukup Lubang tradition in Maras Jauh Village, Seluma Regency, is a cultural heritage to welcome the birth of a baby. This tradition not only functions as a ceremonial activity, but also serves as a means of instilling social and spiritual values ​​​​for the formation of community morals. This study aims to examine the meaning and social and Islamic values ​​​​contained in its implementation. This study has used a descriptive qualitative approach based on a cultural approach. Data collection in this study was conducted through direct observation, in-depth interviews, and documentation. The research sample focused on key informants who had been determined through a snowballing technique, namely traditional midwives (piawang), traditional leaders, religious leaders, and community elements supporting the tradition in Maras Jauh Village. This study has found three key findings. First, this tradition has contained strong social values, such as the practice of mutual cooperation, solidarity, togetherness, and care. Second, the implementation of this tradition also contains essential religious values, including strengthening faith, self-purity (taharah), prayer, and gratitude to God. Third, the practice of the Nukup Lubang tradition demonstrates a harmonious integration of local Serawai customs and Islamic teachings. The Nukup Lubang tradition plays a significant role in transmitting cultural values, fostering character, and strengthening religious identity. Consequently, support for the preservation of this tradition strengthens social cohesion and ensures local wisdom remains relevant to the dynamics of modern development.